Beyond abortion. Law and rights in the post-Dobbs era (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The overruling of Roe v. Wade marked a moment of historic significance, and the mosaic of the post-Dobbs Era represents a litmus test of the consequences. The paper intends to look at these by focusing on how what Dobbs affects goes ‘beyond’ the right to abortion. It is therefore intended to analyze on the medical level the consequences in relation to medical training and profession and on the social level the profound injustice in relation to ‘equitable access’ not only in terms of Abortion Care but of health standards in general. Finally, the example represented by the Food and Drug Administration (FDA) case, the ‘mifepristone and telemedicine case’, underscored the problems created by the new restrictive laws for providers and patients in terms of drug supply and scientific judgment, while also impacting other rights such as free information and free speech, including in the area of new information technologies.
Keywords: Abortion; right to privacy; right to travel; equality; reproductive health